Derivational Affixes in Toy Story 4 Movie Script - Sarah Annisah (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
This research aims to find out some things about derivational affixes contained in Toy Story 4 movie script, such as the types of derivational affixes used in the movie as well as the form and meaning of the derivational affixes. This research uses Yule’s theory (2010). This theory is used to understand everything about affixes, especially on derivational affixes. This research uses a qualitative method. Qualitative method is used to describe and analyze the derivational words in Toy Story 4 movie script. In this research, the researcher focuses on collecting data about derivational affixes in the script of Toy Story 4 movie. The data is taken through derivational text contained in the script. The researcher analyzed a quarter of the total pages of the script. Before analyzing the words containing affixes, the researcher first describes words containing affixes. The result of this study found that there are two types of affixes in Toy Story 4 movie script, namely prefixes and suffixes. There are 2 types of prefixes with 5 word data containing derivational affixes. Prefixes consists of un- (4), in- (1). There are 19 types of suffixes with 124 word data containing derivational affixes. Suffixes consists of -ing (20), -s (41), -ion (4), -ed (18), -es (3), -ful (2), -er (6), -y (5), -en (6), -ly (4), -ic (2), -ite (1), -ship (1), -man (1), -able (1), -ent (1), -ant (1), -est (1), and -tion (1).